Heterotopic Ossification in Hip and Knee Joint After Abdominal Surgery - Özlem Altındağ; Birsev Küçükoğlu (Archives of Rheumatology, 2010)
Heterotopic ossification is a process characterized by the lamellar bone formation in tissues that do not ossify under normal conditions. Although the etiology is not entirely clear, trauma has been considered as an initiating factor for heterotopic ossification. Heterotopic ossification generally occurs in the hip, knee and shoulder joints. Cases with heterotopic ossification have been reported as a slowly developing complication following trauma, spinal cord lesions, stroke, arthroplasty, and burn injury. In this report, a patient with heterotopic ossification developing 20 days after surgery for ruptured aortic aneurysm is presented and discussed in light of the recent literature. (Turk J Rheumatol 2010; 25: 156-8)